How Can STEM Approaches Improve Students' Critical Thinking Skills and Communication Skills? - Gea Ade Rizky; Bambang Saptono (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to analyze the influence of the STEM approach on critical thinking skills and communication skills in mathematics subjects of grade V elementary school students. The research method used was a quasi-experimental design with a pretest-posttest control group design. Sampling used the purposive sampling technique in elementary schools in Yogyakarta City, Indonesia. The instruments used to collect data were test questions and observation sheets. The data normality test used Shapiro-Wilk, while the univariate homogeneity test used Levene's. The data were analyzed by paired t-test and independent t-test. The results of the study showed that the STEM approach had a positive and significant effect on the critical thinking ability and communication skills of grade V elementary school students. These results were theoretical and empirical evidence that the STEM approach had conceptual and practical implications in developing students' critical thinking skills and communication skills.